Your Success in the retail business : (collection) - Hammond, Richard; Berman, Barry (FT Press Delivers, 2014)
A new collection filled with winning ideas and strategies for improving your sucess in the retail business... 2 authoritative books, now in a convenient e-format, at a great price! Smart Retail, the world's #1 guide to retail success, complete with crucial, up-to-date insights--including new case studies, ideas, strategies, and tactics from today's best retailers, like TopShop, IKEA, and Best Buy. Covering everything from creating the ultimate retail experience to understanding the customer and the importance of motivated workers, this is the book that will equip managers, team-workers, retail entrepreneurs and indeed anybody who sells direct to customers, with practical winning ideas and strategies. Competing in Tough Times brings together the powerful new strategies that world-class retailers, like Trader Joe's, Costco, and Nordstrom, are using today to survive--and thrive--in a brutally unforgiving retail environment. Internationally respected retail management expert Barry Berman shows retailers and their suppliers exactly how to build effective strategies based on cost and differentiation, plan and implement those strategies, and measure the results. Berman offers detailed coverage of implementing strategies based on becoming the low-cost provider and minimizing product proliferation; enhancing the service experience; developing and maintaining a strong private label program; and more. From world-renowned experts Richard Hammond and Barry Berman.